(untitled) (Ameghiniana, 2022)
Ancient and modern marine environments are usually characterized by colonizers associated with living and dead organisms, as well as inorganic substrates. There are different terminologies to characterize these colonizations, i.e., if the roots of the terms refer to the colonizer or the colonized substrate. The terminology stated by Paul D. Taylor and Mark A. Wilson is considered here as background to characterize marine ancient and modern assemblages on hard substrates. These authors define the term “sclerobiont”, but not “sclerobiosis”. We focus on the term “sclerobiont” and the need for a formal term, “sclerobiosis”. There is no definition of the latter, which is beginning to be used as a synonym for “epibiosis”. Here we define “sclerobiosis” as the spatial association between any kind of hard substrate and a diversity of life forms, which can occupy different spatial location of the hard substrate. With regard to colonization of marine hard substrates, “epibiosis” is included within “sclerobiosis”. The goal is to clarify in which cases the use of each term is more appropriate, according to the criteria considered in the cited definitions of the terms. When studying different aspects of the colonization of living, dead and inorganic hard substrates, and even when we want to establish comparisons of colonizations over time and space, it is useful to have a term that encompasses all these associations between substrates and colonizers. “Sclerobiosis” is proposed to aid a uniform language among deep-time and modern ecology researchers, especially those working on both settings.